Kinetoplastid Phylogenomics and Evolution - Yurchenko, Vyacheslav; Maslov, Dmitri (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, Kinetoplastid Phylogenomics and Evolution, unites a series of research and review papers related to kinetoplastid parasites. The diverse topics represented in this collection display a variety of scientific questions and methodological approaches currently used to study these fascinating organisms.